Disassembly, recycling, and reuse of magnet material of electric drives - Klier, Tobias; Risch, Florian; Franke, Jörg (Proceedings - 2013 IEEE International Symposium on Assembly and Manufacturing, ISAM 2013, 2013)
The paper discusses different automation concepts for the disassembly of surface mounted magnets, and for the removal of the bandaging of rotors. In detail three strategies to recover the magnet bodies of rotors will be presented. Furthermore the paper introduces an innovative disassembly machine, which can handle different variants of the targeted magnets, to avoid the troubles during the manual removal of magnetized magnets from rotors with surface mounted mag-nets. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Disassembly; Magnet; Rare Earths; Recycling; Sustainability

Disassembly strategies for recovering valuable magnet material of electric drives - Klier, Tobias; Risch, Florian; Franke, Jörg (2013 3rd International Electric Drives Production Conference, EDPC 2013 - Proceedings, 2013)
The paper discusses different automation concepts for the disassembly of magnetized magnet bodies from rotors, and for the removal of the bandaging of rotors. In detail three strategies to recover the magnet bodies of rotors will be presented. Furthermore the paper introduces an innovative disassembly machine, which can handle different variants of the targeted magnets, to avoid the troubles during the manual removal of magnetized magnets from rotors with surface mounted magnets. The paper also presents a concept for recovering internal permanent magnets. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Disassembly; Magnet; Rare Earths; Recycling; Sustainability

Flexible automation for the production of stators and rotors of electric vehicles - Risch, Florian; Tremel, Jan; Klier, Tobias; Franke, Jörg (Advanced Materials Research, 2014)
The increasing electrification of the drive train will-sooner or later-lead to significant changes in the value chains for vehicle manufacturers and suppliers, while sales potentials are still uncertain. Due to the currently small number and high diversity of industrial electric motors with higher power and the complex handling of the necessary materials, the processes are based on manual labor content. For the automotive industry high volume production concepts for electric traction motors will be required in the future. Thus, the importance of automated assembly and manufacturing technologies for electric motors moves into focus. In the production of electric motors e.g. the wiring processes of the stators and the magnet assemblies for permanent-magnet synchronous rotors show potential for further process rationalization. This paper presents alternative approaches for the automation of wiring and magnet assembly processes developed at the Institute for Factory Automation and Production Systems (FAPS) at the Friedrich-Alexander-University of Erlangen-Nuremberg. © (2014) Trans Tech Publications, Switzerland.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Coil winding; Electric drive systems; Electric mobility; Permanent magnet assembly; Production technologies; Robotic assembly